The Effect of Interactive Learning Models on Students' German Writing Skills Class XI - Ardhani, Jusvia; Hutagalung, Insenalia Sampe Roly; Dhillon, Bobby Pramjit Singh (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to determine the effect of the interactive learning model on the German writing skills of the eleventh-grade science students at Taman Madya (Private Senior High School) Tamansiswa Pematangsiantar. This research is quantitative in nature, employing a Pre-Experimental design with a One Group Pretest-Posttest Design. The research instrument used was an essay test consisting of one question. The results of the data analysis showed that the average Pretest score was 43, while the average Posttest score was 87. The research sample consisted of class XI-2 with 35 students. Based on hypothesis testing using the T-test and N-Gain test, the T-test results showed that the calculated t-value was 25.060, while the t-table value with df = 34 at a significance level of 0.05 was 1.691. Since t-calculated > t-table (25.060 > 1.691), H1 is accepted and H0 is rejected. Furthermore, the N-Gain percentage score was 73.57%. Therefore, it can be concluded that the interactive learning model has a significant effect on the German writing skills of the eleventh-grade science students at Taman Madya (Private Senior High School) Tamansiswa Pematangsiantar